2013
DOI: 10.1007/s11013-013-9323-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Diagnosis of Autism: How Parents and Professionals Act and React in France

Abstract: The category of autism has undergone huge changes over the past 20 years. This study was undertaken to analyze the changes and how parents have experienced the diagnostic process in France. Data were obtained from in-depth interviews with parents and psychiatrists, and from 248 questionnaires with open-ended questions filled in by parents. We compared the experiences of parents with adult autistic children to those of parents with young autistic children. Progressively earlier age at diagnosis was evidenced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 60 publications
0
24
1
3
Order By: Relevance
“…This is in contrast to other studies (e.g. Chamak and Bonniau ) that found that the parents were dissatisfied with the diagnostic process, e.g. it took too long, the words used were difficult to understand, and the parents were not treated professionally.…”
Section: Discussioncontrasting
confidence: 98%
“…This is in contrast to other studies (e.g. Chamak and Bonniau ) that found that the parents were dissatisfied with the diagnostic process, e.g. it took too long, the words used were difficult to understand, and the parents were not treated professionally.…”
Section: Discussioncontrasting
confidence: 98%
“…Families in the Osborne and Reed qualitative study identified the need for better training of clinicians, particularly in interpersonal skills 195. A mixed methods French study reported that satisfied families described professionals who made them feel respected, gave them time, and were open minded, direct, and sympathetic,197 whereas harmful practices included not checking to ensure that parents understood the explanation or to see if further time or discussion would be helpful. One qualitative study of how the diagnosis was communicated found that tensions between “realism” and “hopefulness” were negotiated by using a parent friendly frame, complemented by a hopeful formulation or by a defocusing of a “bad news” approach 198.…”
Section: Family Preferences For Asd Diagnostic Assessmentmentioning
confidence: 99%
“…The consequence of all this is that the way in which a society collectively perceives and thinks about something-about what is and is not a stigma-will have practical implications. Moreover, people with ASD are frequently subject to stigmatisation [10].…”
Section: Stigmatisationmentioning
confidence: 99%
“…Persons with ASD can be characterised, according to DSM-5, as possessing deficits in communication and social interaction, repetitive and restrictive patterns of behaviour, interests and activities; with symptoms present early in development, likely to cause significant impairment in social, occupational or other significant areas of functioning, with the caveat that intellectual disability or global developmental delay does not better explain these characteristics [19]. The conceptualisation of ASD has also changed over the last twenty years-it has "shifted from being a rare disease to a broad syndrome and from a psychiatric disorder to a genetic disease involving an atypical development of the nervous system" [10]. Most research into ASD is based in either the cognitive or the biogenetic paradigm-the former characterizes ASD as an information processing deficit related to brain structure, whilst the latter paradigm reduces "the mind to biology" [20].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%